1,107,313 Pages
Welcome! Enter your question below. Please use words like "Who, What, Where, When, Why, How, etc..." in your question. Nothing to ask? Click here for a random, un-answered question.

if f(x)=2x+3 and g(x)=x^2-3x: f(x) + g(x) = (2x+3) + (x^2 - 3x) = x^2 - x +3

Ad blocker interference detected!

Wikia is a free-to-use site that makes money from advertising. We have a modified experience for viewers using ad blockers

Wikia is not accessible if you’ve made further modifications. Remove the custom ad blocker rule(s) and the page will load as expected.